Oral and rectal colonization of Gram-negative antimicrobial-resistant bacteria and Methicillin-resistant Staphylococcus aureus in one long-term care facility and changes in professional oral hygiene care: Cross-sectional and interventional study - Azusa Haruta; Mineka Yoshikawa; Maho Takeuchi; Miki Kawada-Matsuo; Mi Nguyen-Tra Le; Toshiki Kajihara; Yo Sugawara; Junzo Hisatsune; Hitoshi Komatsuzawa; Hiroki Ohge; Motoyuki Sugai; Kazuhiro Tsuga (PLoS ONE, 2026)
The spread of antimicrobial-resistant bacteria is a global threat. Our previous study investigated oral colonization by Gram-negative antimicrobial-resistant bacteria and methicillin-resistant Staphylococcus aureus (MRSA) in long-term care facilities. In this study, antimicrobial-resistant bacteria in the oral cavity of bedridden severely dependent elderly residents were investigated and the relationship of antimicrobial-resistant bacteria with oral and systemic status was clarified. In addition, the effect of professional oral care on antimicrobial-resistant bacteria colonization was investigated. This was a cross-sectional study followed by an interventional study. Fifty-seven residents were randomly assigned to screening for the presence of Gram-negative antimicrobial-resistant bacteria with 3 rd -generation cephalosporin or carbapenem-resistance methods and the presence of oral and rectal MRSA using respective selective plates. Epidemiological data were collected from clinical records. The interventional study was conducted on 23 subjects who presented with Gram-negative antimicrobial-resistant bacteria or S. aureus in the cross-sectional study. The interventions included professional oral care once a week for 8 weeks in addition to daily oral care. Antimicrobial-resistant bacteria colonization before and after the intervention was compared. Among 57 subjects, antimicrobial-resistant bacteria were isolated from oral samples of 29 subjects and from rectal samples of 44 subjects. Among 29 subjects with oral antimicrobial-resistant bacteria, Gram-negative antimicrobial-resistant bacteria and MRSA were isolated from 21 and 17 subjects, respectively. Logistic regression analysis of the independent variables revealed that Non-oral nutritional intake was significantly related to Gram-negative antimicrobial-resistant bacteria positivity. In the interventional study, professional oral care failed to eliminate of oral antimicrobial-resistant bacteria in most subjects. This study showed that subjects with Non-oral nutritional intake had significantly higher rates of oral Gram-negative antimicrobial-resistant bacteria. These findings concluded that a short-term professional oral management has a limited capacity to eliminate antimicrobial-resistant bacteria. Our results provide important information for the control of infections caused by antimicrobial-resistant bacteria in the oral cavity.